Analisis perilaku konsumen: frekuensi pembelian dan preferensi ter-hadap jenis sembako di Ayamaru Raya, Kabupaten Maybrat - isir, Yunike; Sagrim, Meky; Theresia Wambrauw, Ludia (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: This study aims to analyze consumer behavior in purchasing nine essential food commodities (sembako) in Ayamaru Raya, Maybrat Regency, West Papua Province. A descriptive quantitative approach was used involving 30 consumer respondents. The results revealed that most consumers were aged 26–55 years, dominated by females, and primarily consisted of housewives and unemployed individuals. Most consumers purchase sembako three to five times per month, focusing on main commodities such as rice, sugar, cooking oil, eggs, and salt. Brand preferences indicate a tendency toward locally accessible and trusted products such as Merapi and Semangka rice, local sugar, Bimoli cooking oil, Segitiga Biru flour, and Cap Kapal salt. Price, quality, and accessibility are the main factors influencing purchasing decisions. Although prices are relatively high and often fluctuate, purchasing access remains easy as physical stores are located near residential areas. The study recommends strengthening price stability, improving local distribution networks, and empowering traders and consumers to enhance sustainable food security in Ayamaru Raya, Maybrat Regency.